Mortality and adverse events associated with statin use in primary care patients with depression: a real-world, population-based cohort study - De Giorgi, R; De Crescenzo, F; Ostinelli, E; Cowen, P; Harmer, C; Fazel, S; Cipriani, A (BMJ Publishing Group, 2024)
Background New National Institute for Health and Care Excellence (NICE) guidance endorses the prescription of statins in larger population groups for the prevention of cardiovascular and cerebrovascular morbidity and mortality, especially in people with severe mental illness. However, the evidence base for their safety and risk/benefit balance in depression is not established. Objectives This study aims to assess the real-world mortality and adverse events of statins in depressive disorders. Methods Population-based, nationwide (England), between-subject, cohort study. We used electronic health records (QResearch database) of people aged 18–100 years with first-episode depression, registered with English primary care practices over January 1998–August 2020 for 12(+) months, divided into statin users versus non-users. Primary safety outcomes included all-cause mortality and any adverse event measured at 2, 6 and 12 months. Multivariable logistic regression was employed to control for several potential confounders and calculate adjusted ORs (aORs) with 99% CIs. Findings From over 1 050 105 patients with depression (42.64% males, mean age 43.23±18.32 years), 21 384 (2.04%) died, while 707 111 (67.34%) experienced at least one adverse event during the 12-month follow-up. Statin use was associated with lower mortality over 12 months (range aOR2–12months 0.66–0.67, range 99% CI 0.60 to 0.73) and with lower adverse events over 6 months (range aOR2–6months 0.90–0.96, range 99% CI 0.91 to 0.99), but not at 1 year (aOR12months 0.99, 99% CI 0.96 to 1.03). No association with any other individual outcome measure (ie, any other neuropsychiatric symptoms) was identified. Conclusions We found no evidence that statin use among people with depression increases mortality or other adverse events. Clinical implications Our findings support the safety of updated NICE guidelines for prescribing statins in people with depressive disorders.